Kearifan Lokal dalam Bingkai Fiqh Budaya: Perspektif Islam Nusantara dan Relevansinya bagi Umat Global - Nurfania, Andi Elvira; M, Misbahuddin; Shuhufi, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article examines local wisdom within the framework of cultural fiqh through the perspective of Islam Nusantara and its relevance for the global Muslim community. Islam Nusantara is understood as a manifestation of Islamic teachings that harmonize with local traditions and cultures without abandoning the universal principles of Islamic law. This approach emphasizes that fiqh is not rigid, but rather elastic in responding to social, customary, and cultural diversity. Local wisdom—such as traditions of mutual cooperation (gotong royong), deliberation (musyawarah), and respect for social harmony—is interpreted as embodying Islamic values that enrich religious practice. In a global context, the Islam Nusantara model offers a paradigm of religious moderation, tolerance, and intercultural peace. Thus, cultural fiqh serves as a bridge between normative texts and empirical realities, making it not only relevant to Indonesian society but also a potential source of inspiration for the world in building an inclusive and civilized civilization.